The Sustainable Development Strategy of the Light Industry and New Orientations towards Ecotourism - MUKHAN, Bakytzhan; YESSIRKEPOVA, Altyn; TULEMETOVAk, Aigul; ORAZAYEVA, Nazgul; ZHAKESHOVA, Ayimzhan; KANASHAYEV, Daulet (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023DO - 10.14505/jemt.14.2(66).22, 2023)
Being one of the industries in general, the light industry has certain features affecting the environmental crisis, as a result of the rapid growth of enterprises, the increase in production at a huge rate, consumer demand. The reason for this is the massive pollution of the environment with all sorts of emissions and industrial waste, which affects such sub-branches of tourism, such as ecotourism. Light industry, which is one of the promising industries, has a negative impact on the water fund, due to the discharge of untreated effluents into surface water bodies, which requires improvement of mechanisms for the use of nature in this area.